The development of a rating scale for the evaluation of guidance services in the public elementary schools of Manila - Jalandoni, Celestina (Natividad) 1922- (s.n.], 1967)
This study prepared a rating scale for evaluating guidance services in elementary schools. Preparatory considerations were observed in the formulation of items, which were administered and later validated then revised to produce the final rating scale. Items on administrators were included in the final rating scale. Guidance experts and counselors were of strong opinion that administrative, disciplinary, and clerical functions were contrary to basic philosophy and principles of guidance. The proposed evaluation tool is valid and reliable enough, and can therefore be used in evaluating guidance services in public elementary schools of Manila.